KOSMOLOGI DALAM ARSITEKTUR TORAJA - Yulianto Sumalyo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2001)
Modernism in architecture always has a concrete, profane and clear concept.On the totally contrary, traditional architecture traditional has an abstract, spiritual and often religious concept or way of thinking. Toraja, an ethnic group in the northern part of South Sulawesi, has a beautiful and unique architecture which is the expression of Aluk Todolo their way of life and religion. The cosmological thinking of Aluk Todolo is expressed in the architecture of Toraja through it's site plan and units orientation, construction, orientation, material, detail, ornament and other architectural aspects. This article summarises the results of researches, seminars and bibliographical studies on the architecture of Toraja,conducted in the department of architecture University of Hasanuddin Makassar cases from three traditional villages (desa adat): Palawa a big traditional village, Ketekesu' one of the most beautiful traditional villages and Siguntu represent a small desa adat, represent the Toraja traditional architecture. Abstract in Bahasa Indonesia : Modernisme dalam arsitektur selalu menunjuk pada hal-hal yang bersifat konkrit, profan dan konsep yang jelas. Sebaliknya tradisional seperti arsitektur tradisional menunjuk pada hal-hal yang bersifat abstrak, spiritual dan bahkan konsep religius atau